2020
DOI: 10.1094/pdis-09-19-1929-re
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Ralstonia solanacearum and Ralstonia pseudosolanacearum in Brazil

Abstract: Bacterial wilt-causing Ralstonia threaten numerous crops throughout the world. We studied the population structure of 196 isolates of Ralstonia solanacearum and 39 isolates of Ralstonia pseudosolanacearum, which were collected from potato- and tomato-growing areas in 19 states of Brazil. Regardless of the species, three groups of isolates were identified. One group encompassed R. pseudosolanacearum isolates. The other two groups comprise isolates of R. solanacearum (phylotype II) split according to geographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
2
10
3
Order By: Relevance
“…A striking result is the singularity of the most prevalent Malagasy isolates belonging to sequevar 18 (corresponding to cluster 1). Indeed, despite the fact that sequevar 18 is distributed worldwide [37,[67][68][69][70][71][72][73]75], our study revealed no genetic links between Malagasy isolates and worldwide isolates (South-West Indian Ocean, Africa, Americas, Asia isolates). The closest haplotype (one strain) was a double-locus variant from Guadeloupe.…”
Section: Rs1-mlva14 Unveiled Contrasting Genetic Diversity and Epidemcontrasting
confidence: 67%
See 1 more Smart Citation
“…A striking result is the singularity of the most prevalent Malagasy isolates belonging to sequevar 18 (corresponding to cluster 1). Indeed, despite the fact that sequevar 18 is distributed worldwide [37,[67][68][69][70][71][72][73]75], our study revealed no genetic links between Malagasy isolates and worldwide isolates (South-West Indian Ocean, Africa, Americas, Asia isolates). The closest haplotype (one strain) was a double-locus variant from Guadeloupe.…”
Section: Rs1-mlva14 Unveiled Contrasting Genetic Diversity and Epidemcontrasting
confidence: 67%
“…Interestingly, sequevar 31 isolated in the lowlands and up to altitudes above 1000m in Réunion [37], as well as in Côte d'Ivoire [67], exhibited a similar environmental distribution. So far, sequevar 18 has always been reported from lowlands in the Americas [68][69][70], Africa [67], Asia [71][72][73], Oceania [74] and on islands in the South-West Indian Ocean [37,75]. In contrast, even though a very limited number of isolates was used in our study, sequevar 33 was only isolated at moderate and high elevations (above 900m) and sequevar 46 was only isolated in lowlands (below 300m).…”
Section: Rs1-mlva14 Unveiled Contrasting Genetic Diversity and Epidemcontrasting
confidence: 58%
“…The occurrence of R. solanacearum in soil, water and the rhizosphere of cultivated and non-cultivated plants in all regions in Brazil provides additional support to the hypothesis that the country is a putative center of origin of this bacterial species (Wicker et al 2012;Santiago et al 2020). In addition to the practical implications of the findings of the present study, i.e.…”
supporting
confidence: 83%
“…Planting of pathogen‐free rooted cuttings and use of resistant genotypes are the best management strategies to control BW in Eucalyptus (Fonseca et al., 2016). However, a high genetic variability of the RSSC found in Brazil (Fonseca et al., 2014; Santiago et al., 2020) may hamper the effective development of resistant clones in breeding programmes. The correct taxonomic classification of the pathogen and a good knowledge of its genetic and aggressiveness variability is a key factor when undertaking epidemiological studies of this species complex that could contribute to disease management.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they allow the selection of the most aggressive isolates to be used in inoculations for screening genotypes with effective resistance. Because of the high genetic diversity of R. solanacearum associated with solanaceous plants (Santiago et al., 2020) and the recent detection of R. pseudosolanacearum also causing BW in eucalypt (Freitas et al., 2020), we hypothesized that a study of the genetic variability of the RSSC population associated with eucalypt in Brazil could provide important information to help guide studies aimed at establishing appropriate disease management strategies. As such, this work aimed to molecularly characterize a large collection of RSSC isolates obtained from Eucalyptus , to determine to which phylotypes and sequevars they belong, to gain insights into their geographic distribution as well as to assess the aggressiveness variability of a select group.…”
Section: Introductionmentioning
confidence: 99%